2006
DOI: 10.1007/s00441-006-0184-6
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependency of apoptosis and the blood-testis barrier in the dogfish shark (Squalus acanthias): cadmium-induced changes as assessed by vital fluorescence techniques

Abstract: Naturally occurring heavy metals and synthetic compounds are potentially harmful for testicular function but evidence linking heavy metal exposure to reduced semen parameters is inconclusive. Elucidation of the exact stage at which the toxicant interferes with spermatogenesis is difficult because the various germ cell stages may have different sensitivities to any given toxicant, germ cell development is influenced by supporting testicular somatic cells and the presence of inter-Sertoli cell tight junctions cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
0
37
1
Order By: Relevance
“…Although low molecular weight DNA fragmentation (usually TUNEL-detected) in many cultured mammalian cells has been shown to be coincident with advanced chromatin margination, called stage II chromatin condensation (Samejima et al, 2001;Yuste et al, 2005), we contend that the discordances reported here for the two methods are biologically significant in vivo. One explanation for these differences may be that chromatin condensation into a single pyknotic mass, and not chromatin margination of multiple large masses which was never observed, may be specifically associated with a prolonged duration of apoptosis, which is known for other fish species as well ([McClusky, 2005] and [McClusky, 2006]). Interestingly, pyknosis induced by slow death in avian erythrocytes show no involvement of nucleases, and thus presumably no massive DNA fragmentation (Burgoyne, 1999).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although low molecular weight DNA fragmentation (usually TUNEL-detected) in many cultured mammalian cells has been shown to be coincident with advanced chromatin margination, called stage II chromatin condensation (Samejima et al, 2001;Yuste et al, 2005), we contend that the discordances reported here for the two methods are biologically significant in vivo. One explanation for these differences may be that chromatin condensation into a single pyknotic mass, and not chromatin margination of multiple large masses which was never observed, may be specifically associated with a prolonged duration of apoptosis, which is known for other fish species as well ([McClusky, 2005] and [McClusky, 2006]). Interestingly, pyknosis induced by slow death in avian erythrocytes show no involvement of nucleases, and thus presumably no massive DNA fragmentation (Burgoyne, 1999).…”
Section: Discussionmentioning
confidence: 90%
“…The detection of fragmented DNA with in situ end-labelling techniques, such as the terminal transferase-mediated dUTP nick-end-labelling assay (TUNEL), facilitates the quantification of the actual numbers of germinal clones that will be deleted via apoptosis from the spermatogenic progression ([McClusky, 2005] and [McClusky, 2006]). Recent advances have made possible the immunohistochemical detection of earlier phases of apoptosis such as the activation of cysteine aspartyl-specific proteases (caspases), including cleaved caspase-3 which is a major executioner of apoptotic morphology (Gown and Willingham, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The testes are particularly vulnerable to Cd as it increases germ cell apoptosis (Ozawa et al, 2002;Gupta et al, 2004;McClusky, 2006), causes spermiation failure stage-dependent relationship with these supporting cells, and recent in vitro model systems (Yu et al, 2005) have recognized this.…”
Section: Introductionmentioning
confidence: 96%
“…Third, because spermatocysts are linearly arranged in a maturational order across the diameter of the elongated testis, spermatocysts containing germ cells in different stages of development are topographically separated, resulting in a readily visible zonation in testicular cross-sections. Several zones of maturation are readily distinguishable on the basis of transillumination characteristics, colour and position relative to the germinal zone (GZ, the folliculogenic, cyst-producing germinal ridge running the length of the testis) and the epigonal organ, a lymphomyeloid tissue mass encapsulating the mature pole of the testis, and cysts in these zones can be dispersed and staged under a dissecting microscope (McClusky, 2006). As a first step in developing a test system for toxicological studies using this model, validated fluorescence microscopic techniques for assessing stage-specific functions in living testicular tissue were developed (McClusky, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus there is the formation of a degenerate zone comprising several layers of apoptotic multilayered spermatogonial clones that is tolerated for several months in the testis (McClusky 2005(McClusky , 2006. By all accounts, such a highly degenerative state, which is also seen in another dogfish, Scyliorhinus canicula (Dobson & Dodd 1977), seems not, contrary to accepted dogma (Kroemer et al 2008), to resemble a 'clean' and orderly form testicular death and is suggestive of a delayed and protracted elimination process even as other clones develop normally.…”
Section: Introductionmentioning
confidence: 98%